PENYEWAAN GEDUNG OLAHRAGA MENGGUNAKAN WEB (Information Technology and Telematics, 2014)
Abstract - In this modern age of science is inseparable from the rapid advancement of computer science. Many people use technology to search for information, do a job, as a media promotion, and others. Here the author will promote a sports hall with computer  media to be shown wuth the web-based diinternet. I want to help building owners to promote as well as compiling a list of rental houses online. Sports Centre gave priority to Astina rental for the sport of badminton and futsal. Inside the building there are four fields tha can be rented out and one futsal field. There is a rental system for member or daily. As for conditions on the member’s system that should have an exercise routine (minimum one week). If a permit has to be confirmed two days earlier (no confirmation it will be removed from the registered user). This information system development method using prototype and his programming language for using PHP with a MySQL database as well as for it design using UML (Unifed Modeling Language). Keywords : Sports Hall Rental Information System, Astina, PHP, MySQL